2022
DOI: 10.1101/2022.07.26.501632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating Predictive Coding in Younger and Older Children Using MEG and a Multi-Feature Auditory Oddball Paradigm

Abstract: There is mounting evidence for predictive coding theory from computational, neuroimaging, and psychological research. However there remains a lack of research exploring how predictive brain function develops across childhood. To address this gap, we used paediatric magnetoencephalography (MEG) to record the evoked magnetic fields of 18 younger children (M = 4.1 years) and 19 older children (M = 6.2 years) as they listened to a 12-minute auditory oddball paradigm. For each child, we computed a MisMatch Field (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 95 publications
0
0
0
Order By: Relevance
“…Specifically, I have explored the possibility that this kind of lived experience (or, perezhivanie) might lead to autistic students typifying social learning experiences differently compared to nonautistic people. Indeed, this finding aligns with neuroscientific and predictive coding accounts (or, Bayesian statistics, see section 2.2.3.1) of autistic peoples' distinct predictions and constructions of their physical environment (Palmer et al, 2017;Pellicano & Burr, 2012;Rapaport et al, 2022). That is, neuroscientific techniques together with advanced statistical modelling as is used in predictive coding studies have found that autistic people's predictions or expectations (or, typifications) of their physical environment are distinct from that of nonautistic people (Pellicano 127 & Burr, 2012;Rapaport et al, 2022).…”
Section: Predictive Coding and Typificationsupporting
confidence: 75%
See 4 more Smart Citations
“…Specifically, I have explored the possibility that this kind of lived experience (or, perezhivanie) might lead to autistic students typifying social learning experiences differently compared to nonautistic people. Indeed, this finding aligns with neuroscientific and predictive coding accounts (or, Bayesian statistics, see section 2.2.3.1) of autistic peoples' distinct predictions and constructions of their physical environment (Palmer et al, 2017;Pellicano & Burr, 2012;Rapaport et al, 2022). That is, neuroscientific techniques together with advanced statistical modelling as is used in predictive coding studies have found that autistic people's predictions or expectations (or, typifications) of their physical environment are distinct from that of nonautistic people (Pellicano 127 & Burr, 2012;Rapaport et al, 2022).…”
Section: Predictive Coding and Typificationsupporting
confidence: 75%
“…Typically, experience in interacting with the world results in learning more accurate predictions (top-down processing) of "reality" over time, but in the case of autistic peoples' experiences and perceptions, Pellicano and Burr (2012) found that autistic people rely more on incoming sensory information (bottom-up) rather than learned predictions. Other researchers (Lawson et al, 2014;Rapaport et al, 2022) have found quite the opposite. That is, they found that autistic people use prior, but over-specified (or, over detailed) predictions from previously encountered experiences.…”
Section: Bayesian Accounts Of Perceptual Processing Predictive Coding...mentioning
confidence: 86%
See 3 more Smart Citations